A eurypterid trackway from the Middle Ordovician of New York State. (January 2023) - Braddy, Simon J.; Gass, Kenneth C.
Abstract: Palmichnium gallowayi (Sharpe, 1932 ) new combination from the Middle Ordovician Martinsburg Formation (proximal deltaic facies) of Rondout, near Kingston, New York State, is redescribed. It consists of opposing series of five tracks, the outer two large and pear-shaped, the inner three smaller and elliptical, arranged in a chevron converging in the direction of travel, on either side of a wide medial impression. It is attributed to a medium-sized stylonurid eurypterid using a decapodous gait, crawling onto the shoreline, traversing the intertidal zone, a behavior interpreted as part of its reproductive life cycle. This provides the earliest ichnological evidence for the 'mass-molt-mate' hypothesis, which proposes that eurypterids migrated en masse into nearshore environments to molt and mate.